Burgeoning Exploration of the Role of Natural Killer Cells in Anti-PD-1/PD-L1 Therapy - Bai, Rilan; Cui, Jiuwei (Frontiers in Immunology, 2022)
Antibodies targeting programmed death receptor-1 (PD-1)/programmed death ligand-1 (PD-L1) have been considered breakthrough therapies for a variety of solid and hematological malignancies. Although cytotoxic T cells play an important antitumor role during checkpoint blockade, they still show a potential killing effect on tumor types showing loss of/low major histocompatibility complex (MHC) expression and/or low neoantigen load; this knowledge has shifted the focus of researchers toward mechanisms of action other than T cell-driven immune responses. Evidence suggests that the blockade of the PD-1/PD-L1 axis may also improve natural killer (NK)-cell function and activity through direct or indirect mechanisms, which enhances antitumor cytotoxic effects; although this topic has often been neglected in previous studies, it is important. Recently, some studies have reported evidence of PD-1 and PD-L1 expression in human NK cells, performed exploration of the intrinsic mechanism by which PD-1/PD-L1 blockade enhances NK-cell responses, and made some progress. This article summarizes the recent advances regarding the expression of PD-1 and PD-L1 molecules on the surface of NK cells as well as the interaction between anti-PD-1/PD-L1 drugs and NK cells and associated molecular mechanisms in the tumor microenvironment.